2006
DOI: 10.1063/1.2189012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-island single-electron devices from self-assembled colloidal nanocrystal chains

Abstract: We report the fabrication of multi-island single-electron devices made by lithographic contacting of selfassembled alkanethiol-coated gold nanocrystals. The advantages of this method, which bridges the dimensional gap between lithographic and NC sizes, are (1) that all tunnel junctions are defined by self-assembly rather than lithography and (2) that the ratio of gate capacitance to total capacitance is high. The rich electronic behavior of a double-island device, measured at 4.2 K, is predicted in detail by c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 13 publications
2
41
0
Order By: Relevance
“…These values are reasonably consistent with previously reported values for a similar structure. 13 Moreover, a close inspection of the conductance map reveals some hints of a double island structure as reported in Ref. 13.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…These values are reasonably consistent with previously reported values for a similar structure. 13 Moreover, a close inspection of the conductance map reveals some hints of a double island structure as reported in Ref. 13.…”
mentioning
confidence: 78%
“…13 Moreover, a close inspection of the conductance map reveals some hints of a double island structure as reported in Ref. 13. This behavior may result from a weak coupling of electrodes to the gold nanoparticles adjacent to the main nanoparticle island.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Nanoparticle devices including electronics [1][2][3] and photonics [4,5] have attracted much attention, and the techniques for arranging nanoparticles in designed locations play an important role for future integration of nanodevices and circuits. The techniques employed fall into two main categories: the AFM (atomic force microscope) tip manipulation of nanoparticles and the self-assembly method, which invokes inter-particle or particle/substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lee et al (2005) selectively assembled 10 nm thiol-modified single-stranded DNA nanoparticles into nanogaps utilizing the DNA hybridization scheme; Bates et al (2006) used Mg 2+ -mediated RNA-RNA loop-receptor interaction; Weiss et al (2006) reported on the lithographic contacting of previously SA 50 nm nanoparticles; and Coskun et al (2008) applied pre-structured substrate surfaces to achieve strictly one-dimensional arrangements of 13 and 50 nm sized AuNPs.…”
Section: (E) Strategies For Nanoparticle Assemblymentioning
confidence: 99%